The Improvement of Students` English Pronunciation by Using Animation (3d) Video for the Second Years Students of Junior High School 1 Payakumbuh - Edrian Rahmawati; Ratmanida Ratmanida (Universitas Negeri Padang, 2020)
The purpose of this study is to see whether animation video can improve pronunciation level of second years students in Junior High School 1 Payakumbuh. This Classroom Action Research study have 251 students which consist of 7 classes as the population. The participant is 36 students that chosen by using cluster random sampling technique. In collecting the data, researcher used observation to observe the students` behavior during teaching learning process with field notes, then used test to find the improvement of students’ speaking pronunciation during the implementation, and used questionnaire to find out students` opinion about using animation video as learning media. The research was conducted in two cycles, where each cycle consisted of 4 meetings. The research findings showed that the implementation of animation video could improve students’ pronunciation level from “very good” level up to “excellent” level. It can be concluded that the implementation of animation video in learning process has beneficial effect on students’ pronunciation.